2015
DOI: 10.1007/s10237-015-0751-4
|View full text |Cite
|
Sign up to set email alerts
|

An advanced computational bioheat transfer model for a human body with an embedded systemic circulation

Abstract: In the present work, an elaborate one-dimensional thermofluid model for a human body is presented. By contrast to the existing pure conduction-/perfusion-based models, the proposed methodology couples the arterial fluid dynamics of a human body with a multi-segmental bioheat model of surrounding solid tissues. In the present configuration, arterial flow is included through a network of elastic vessels. More than a dozen solid segments are employed to represent the heat conduction in the surrounding tissues, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 41 publications
1
33
0
1
Order By: Relevance
“…Further details on boundary conditions may be obtained from references (Mynard and Nithiarasu 2008;Low et al, 2012;Coccarelli and Nithiarasu 2015;?, Coccarelli et al, 2016).…”
Section: Locally Conservative Galerkin (Lcg) Methods For Systemic Circmentioning
confidence: 99%
See 3 more Smart Citations
“…Further details on boundary conditions may be obtained from references (Mynard and Nithiarasu 2008;Low et al, 2012;Coccarelli and Nithiarasu 2015;?, Coccarelli et al, 2016).…”
Section: Locally Conservative Galerkin (Lcg) Methods For Systemic Circmentioning
confidence: 99%
“…The physical model consists of a network of elastic tubes representing blood flow in large arteries, i.e., 63 arteries including the coronaries (Mynard and Nithiarasu, 2008;Low et al, 2012;Coccarelli and Nithiarasu, 2015;Boileau et al, 2015;Coccarelli and Nithiarasu, 2015;Coccarelli et al, 2016). To represent the arterial system, the model proposed by (Mynard and Nithiarasu, 2008;Low et al, 2012) is adopted and for 63 arterial segments are used as shown in Fig.…”
Section: Outline Of the Physical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Three-dimensional models represent thermal changes in a human body close to reality but are, however, difficult to apply. Therefore, the segmented models that consider various biological and physical processes may be the preferred models [93]. Investigators have considered alternative models to describe whole-body heat transfer, from just two nodes describing core and periphery (for example, Gagge [94]) to multi-segmented, multi-layered models.…”
Section: Bioheat Transfermentioning
confidence: 99%